2022
DOI: 10.3390/ijerph19137630
|View full text |Cite
|
Sign up to set email alerts
|

γ-Polyglutamic Acid Production, Biocontrol, and Stress Tolerance: Multifunction of Bacillus subtilis A-5 and the Complete Genome Analysis

Abstract: Bacillus subtilis A-5 has the capabilities of high-molecular-weight γ-PGA production, antagonism to plant pathogenic fungi, and salt/alkaline tolerance. This multifunctional bacterium has great potential for enhancing soil fertility and plant security in agricultural ecosystem. The genome size of B. subtilis A-5 was 4,190,775 bp, containing 1 Chr and 2 plasmids (pA and pB) with 43.37% guanine-cytosine content and 4605 coding sequences. The γ-PGA synthase gene cluster was predicted to consist of pgsBCA and fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Precursor of glutamate is 2-oxoglutarate that is transformed to glutamic acid by glutamate synthase encoded in gltAB genes. 47,48 Some authors have been reported that acidic environments downregulated gltAB. 45 On the other hand, expression of citB gene, encoded for aconitase enzyme, responsible for citrate conversion to isocitrate in the tricarboxylic acid cycle is under control of the AbrB repressor, which is counteracted by sigma-H. As explained earlier, acid conditions would lead to lower sigma-H activity, maintaining AbrB negative control on aconitase, decreasing the carbon flux towards 2-oxoglutarate, the glutamate precursor and hence to γ-PGA.…”
Section: Discussionmentioning
confidence: 99%
“…Precursor of glutamate is 2-oxoglutarate that is transformed to glutamic acid by glutamate synthase encoded in gltAB genes. 47,48 Some authors have been reported that acidic environments downregulated gltAB. 45 On the other hand, expression of citB gene, encoded for aconitase enzyme, responsible for citrate conversion to isocitrate in the tricarboxylic acid cycle is under control of the AbrB repressor, which is counteracted by sigma-H. As explained earlier, acid conditions would lead to lower sigma-H activity, maintaining AbrB negative control on aconitase, decreasing the carbon flux towards 2-oxoglutarate, the glutamate precursor and hence to γ-PGA.…”
Section: Discussionmentioning
confidence: 99%
“…subtilis was recognized to promote plant growth or biocontrol of soil-borne disease (Balderas-Ruíz et al, 2021 ). In our previous research, strain A-5 was also used as a multifunctional PGPR with biocontrol properties and salt-alkaline resistance (Bai et al, 2022 ). Therefore, A-5 addition (A5 and FJY treatments) significantly altered the bacterial community structure in the rhizosphere soil.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the glutamate racemase encoded by the pgsA gene facilitates the conversion of L-glutamate-γ-semialdehyde to D-glutamate-γ-semialdehyde [ 2 ]. Ultimately, the multifunctional enzyme encoded by pgsE , possessing glutamate racemase and glutamate-5-semialdehyde dehydrogenase activities, catalyzes the conversion of D-glutamate-γ-semialdehyde to L-glutamate, thereby completing the synthesis of γ-PGA, which is then released extracellularly [ 25 ]. The synthesis of γ-PGA is an ATP-dependent process, and the synthesis of bioprecursors containing glutamic acid residues conveniently provides energy for this process [ 24 ].…”
Section: Introductionmentioning
confidence: 99%